Development of Biological Assessment Based on Science Process Skills In Senior High School City of Palembang - Linda Aprianingsih; Sri Wardhani; Sulton Nawawi (Mangifera Edu, 2021)
The research background is that it can develop biological assessment based on science process skills because science process skills are important for logical thinking to train students' thinking skills. From the results of the initial needs analysis of class X questions, science process skills are still low, the teacher has not fully developed the science process skills-based assessment because it still uses questions from biology books. This study aims to determine the characteristics and feasibility of assessment based on science process skills developed in biology class X semester 2. This research is development research. Development is carried out using a procedural model by adapting Mcintire's research and development model, with 4 stages of test development including defining competencies, test participants and test objectives, developing test plans, compiling test items, writing administrative instructions. This research stage is limited because it only wants to know the characteristics and feasibility of the assessment. The research instrument used an interview sheet, a questionnaire sheet, and an observation sheet. Expert validation was carried out by 6 expert validators: (1) material experts; (2) linguists; and (3) evaluation experts; The data analysis technique uses qualitative descriptive that refers to the formula adapted by Sugiyono (2018) with a scale of 4. The results of this study are in the form of a biological assessment based on science process skills in the form of multiple-choice questions in which there is biology material for class X semester 2. Biological assessment characteristics are based on science process skills, namely using indicators consisting of observing, grouping, interpreting, predicting, asking questions, hypothesizing, planning experiments, applying concepts, and communicating. The feasibility of a biological assessment based on science process skills based on expert validators, the results are valid to very valid so that the biological assessment based on science process skills developed is feasible to be used to measure the science process skills of class X students.